A BIBLIOMETRIC ANALYSIS OF RESEARCH ON BIOCHAR FOR WASTEWATER TREATMENT - Laili Fitria (Jurnal Sosioteknologi, 2021)
This paper investigates global research of highly cited articles on biochar for wastewater treatment using bibliometric analysis from Scopus database. Based on bibliometric, highly cited articles were published between 2009-2018. We found 33 highly cited articles with 6,429 citations from various journals, countries, institutions, and authors. The most active journal to publish biochar in wastewater treatment is Journal of Hazardous Materials (JHM) from Netherlands. Most active authors come from America and China. University of Florida, USA, is the most active institution to research the use of biochar in wastewater treatment. Then, the common keywords that authors used are biochar and heavy metals. It shows that biochar is effective to remove heavy metals from wastewater. Also, biochar optimization in production and adsorption is a concern of future research. This is one of the first attempts to understand a stream of research which, over time, has paved the way for the utilization of biochar as a material for wastewater treatment.